Otolaryngology and head and neck surgery - Warner, Giles (Oxford specialist handbooks., 2009)
The Oxford Specialist Handbook of Otolaryngology and Head and Neck Surgery is packed full of information which provides an invaluable aid to daily life in ENT practice. It contains comprehensive, practical approaches to subjects, presented in a compact and precise fashion to allow fast, streamlined access to current up-to-date information providing a superb text for education. This book provides an enjoyable way to learn the important aspects of a great medicalspecialty.